Students Mathematical Literacy Viewed from Cognitive Style: Systematic Literature Review - Ahbi Mahdianing Rum; Dadang Juandi (Department of Mathematics, Universitas Negeri Gorontalo, 2023)
This study aims to describe the results of research on students' mathematical literacy analyzed based on cognitive styles. This study used Systematic Literature Review (SLR) method. The sample in this study were 11 articles regarding students' mathematical literacy viewed from cognitive styles which were published in 2018 to September 2022 and were located in Indonesia. The results of this study will be reviewed based on the year of publication, level of education, research location, and to find out the description towards students mathematical literacy viewed from cognitive style. By using the SLR method, it was found research on students' mathematical literacy viewed from cognitive styles got a lot of attention every year, most of this research was conducted at the senior high school (SMA) education level, and most of this research was carried out in the Java island. In addition, by synthesizing the results of research on students' mathematical literacy viewed from cognitive style with the help of Atlas.ti, it was found that cognitive style influences students characteristic in using their mathematical literacy